A research about the labor market in wich students from the B. A. in english emphasis in teaching from The Foreing Languaje Department at The university of El Salvador - Barahona López, Maria Ermelinda; Rodríguez López, Ana Ruth; Moreno Morán, Cristian Lisandro; Gamero Ortiz, José Ricardo; Garay Salinas, Ricardo (San Salvador, El Salvador : Universidad de El Salvador, 2013)
The present document describes a formal research, which has been done based on the facts about labor market for bilingual people, personal issues regarding priorities on students’ lives, family ties that might interfere with their formal studies, level of proficiency acquired by students, the contrast between working and studying at the same time and its effects on students’ outcomes, taking into account also the time students have in the major. It is also important to mention that the sample is composed not only by students, but also graduates, who are already exerting their abilities in the teaching field or in any other one that has to do with the English Language use.
Incluye anexos.
Tesis para optar al titulo de (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2013
Bibliográfia : hoja 61
Keywords: Inglés -- Enseñanza; Empleo de estudiantes; Mercado laboral -- El Salvador